2022
DOI: 10.1158/2326-6066.cir-22-0277
|View full text |Cite
|
Sign up to set email alerts
|

HRS Regulates Small Extracellular Vesicle PD-L1 Secretion and Is Associated with Anti–PD-1 Treatment Efficacy

Abstract: PD-L1 localized to immunosuppressive small extracellular vesicles (sEV PD-L1) contributes to tumor progression and is associated with resistance to immune checkpoint blockade (ICB) therapy. Here, by establishing a screening strategy with a combination of tissue microarray (TMA), IHC staining and measurement of circulating sEV PD-L1, we found the endosomal sorting complex required for transport (ESCRT) member protein hepatocyte growth factor-regulated tyrosine kinase substrate (HRS) was the key regulator of cir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…As showing in Figure 3E, the PD‐L1 mRNA expression was no significant difference in AGS cells that overexpressed Flag‐RNF43 or Flag‐vector; nevertheless, PD‐L1 protein expression level in AGS cells that overexpressed Flag‐RNF43 was lower than that in control (Figure 3F). It is known that some cancer cells could secrete PD‐L1 in the cell culture supernatant 31,32 . The level of PD‐L1 in the cell culture supernatant was assessed by ELISA, and as showing in Figure 3G, no significant difference was observed in AGS cells that overexpressed Flag‐RNF43 or Flag‐vector, suggesting that the downregulation of PD‐L1 expression by overexpressing RNF43 was not due to increase PD‐L1 secretion in the supernatant.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As showing in Figure 3E, the PD‐L1 mRNA expression was no significant difference in AGS cells that overexpressed Flag‐RNF43 or Flag‐vector; nevertheless, PD‐L1 protein expression level in AGS cells that overexpressed Flag‐RNF43 was lower than that in control (Figure 3F). It is known that some cancer cells could secrete PD‐L1 in the cell culture supernatant 31,32 . The level of PD‐L1 in the cell culture supernatant was assessed by ELISA, and as showing in Figure 3G, no significant difference was observed in AGS cells that overexpressed Flag‐RNF43 or Flag‐vector, suggesting that the downregulation of PD‐L1 expression by overexpressing RNF43 was not due to increase PD‐L1 secretion in the supernatant.…”
Section: Resultsmentioning
confidence: 91%
“…It is known that some cancer cells could secrete PD-L1 in the cell culture supernatant. 31,32 The level of PD-L1 in the cell culture supernatant was assessed by ELISA, and as showing in Figure 3G, no significant difference was observed in AGS cells that overexpressed Flag-RNF43 or Flag-vector, suggesting that the downregulation of PD-L1 expression by overexpressing RNF43 was not due to increase PD-L1 secretion in the supernatant. Collectively, the data suggested that RNF43 regulated PD-L1 expression is restricted to posttranslational modification.…”
Section: Rnf43 Downregulated Pd-l1 Via Ubiquitination Of Pd-l1 In Gas...mentioning
confidence: 92%
“…In addition, basic research has found the same phenomenon. Knockdown of HRS markedly reduced PD-L1 expression in head and neck squamous cells carcinoma (HNSCC) cell-derived sEVs, and these sEVs from HRS knockdown cells showed decreased immunosuppressive effects on CD8+ T cells [20]. HRS, serving as a crucial component of ESCRT-0, plays a pivotal role in the initial recognition and sorting of protein cargo destined for incorporation into ILVs within MVBs [20].…”
Section: Gc Cells-derived Evs Communicate With Immune Cellsmentioning
confidence: 99%
“…Knockdown of HRS markedly reduced PD-L1 expression in head and neck squamous cells carcinoma (HNSCC) cell-derived sEVs, and these sEVs from HRS knockdown cells showed decreased immunosuppressive effects on CD8+ T cells [20]. HRS, serving as a crucial component of ESCRT-0, plays a pivotal role in the initial recognition and sorting of protein cargo destined for incorporation into ILVs within MVBs [20]. Furthermore, research has unveiled that the phosphorylation of hepatocyte growth factor-regulated tyrosine kinase substrate (HRS) is responsible for driving the secretion of immunosuppressive exosomes bearing PD-L1, thereby limiting the infiltration of CD8+ T cells into tumor tissues [21].…”
Section: Gc Cells-derived Evs Communicate With Immune Cellsmentioning
confidence: 99%
“…Treatment is determined by many criteria, including the tumor's location and extent, the stage of the disease, and the patient's overall health and preferences. In recent years, there has also been a rise in concern about the use of immune checkpoint inhibitors, which target the programmed death-ligand 1 (PD-L1) and other immune-suppressing proteins, as therapeutic options for HNSCC [ 3 ]. The PD-1 protein plays a role in regulating the immune system as it is present on the surface of T-cells, B-cells, and natural killer cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%